2002
DOI: 10.1038/sj.bmt.1703573
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation for progressive follicular lymphoma

Abstract: Despite its prolonged disease course compared to other types of lymphoma, most patients eventually succumb to the disease. 1,2 A number of treatment strategies have been explored including radiotherapy, alkylator-based chemotherapy, purine nucleoside analogues and most recently, monoclonal antibodies. Unfortunately, none of these treatments are considered curative for patients with advanced disease and most studies have failed to show a survival advantage over historical controls. [3][4][5][6][7][8] Recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Similar observations were made in single center or registry studies. [50][51][52] The recent study from Japan reported on 38 patients with indolent lymphoma (37 patients had FL) and reported a 2-year OS of 57% with no relapses seen beyond 2 years after transplantation.…”
Section: Myeloablative Conditioning and Allo-sct In Indolent Lymphomamentioning
confidence: 99%
“…Similar observations were made in single center or registry studies. [50][51][52] The recent study from Japan reported on 38 patients with indolent lymphoma (37 patients had FL) and reported a 2-year OS of 57% with no relapses seen beyond 2 years after transplantation.…”
Section: Myeloablative Conditioning and Allo-sct In Indolent Lymphomamentioning
confidence: 99%
“…Moreover, the outcome of allo-HSCT in each histologic subtype has not been fully determined. Previous studies have suggested that allo-HSCT improves the prognosis of patients with advanced follicular lymphoma (FL), 7,10,11 whereas few reports have been published on its benefit in aggressive lymphoma. 12,13 In particular, there has been very little information available on subtypes, including mantle-cell lymphoma 11,14 ; peripheral T-cell lymphoma, unspecified (PTCL) 15 ; natural killer (NK) cell lymphoma 16 ; and anaplastic large cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…However, only one study with ASCT in first remission was initiated in the rituximab era 38 . The allogeneic transplantation was examined in relapsed FL and it proved potentially curative, but the first reports on allogeneic transplantation with myeloablative regimens did not resolve whether there is a benefit in OS, mainly due to the high treatment related mortality (21-40%) [39][40][41][42] . Thus, the main focus at the present moment is to explore the efficacy of rituximab maintenance therapy in first remission with or without ASCT, as well the efficacy of radioimmunochemotherapy and allogeneic stem cell transplantation with the reduced-intensity conditioning (RIC) protocols, based on rituximab and fludarabine [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%